Addressability: Identification and Communicative Positions in Critical Sociological Perspective (Sociologisk Forskning, 2025)
In this article we develop the concept of addressability to help us unpack processes of identification. We start from a foundational sociological account of addressing as laid out by Simmel, and use Luhmann’s systems theory to identify tensions in the overlap between different systems. The dual character of addressing as reductive (in meaning) and constructive (of communicative positions) helps us understand a mode of knowledge production that generates its own recipients. By concentrating on the moment of addressing in this manner and developing the concept of addressability to explain its complexity, we seek to build an analytic concept that is useful for scholars who are interested in unpacking the construction of communicative positions in identification. We demonstrate the potential of this concept with an analysis of two moments of addressability in action that involve personal identification numbers. We conclude that the intersection and mutual challenge of these two approaches can help us connect different addressing moments while also moving beyond questions of surveillance and entitlement that routinely seek to capture the problem of identification.
Keywords: addressability; identification; identification numbers; systems theory; surveillance